Kuszenie historią: zwrot narracyjny we współczesnej powieści galicyjskiej - Poliszczuk, Jarosław (Slavia Occidentalis, 2016)
A review of modern historiography shows the traditional methods of the description of history and of appeals to certain private, subjective and emotional facts. In the context of this problem, the author researches novels of contemporary Ukrainian literature which have a historical background. These are The Pharmacist (2015) by Yuriy Vynnychuk, Felix Austria (2014) by Sophia Andruchovych and Kornelia (2015) by Nadia Morykvas. These writers don’t suggest an absolutely new concept of the past, but their interpretations of history show signs of a new method which hasn’t been invented just for today. Writers show history as the private experience of separate heroes, as in such an interpretation it takes the new plot. Such a literary position demonstrates a dissatisfaction with memorial culture, which is typical nowadays.